First records of Perithous Holmgren (Hymenoptera: Ichneumonidae: Pimplinae) and Neoxorides Clément (Poemeniinae) from Mexico - Khalaim, Andrey I.; Ruíz-Cancino, Enrique; Coronado-Blanco, Juana María (Zootaxa, 2023)
Two genera, Perithous Holmgren (Pimplinae) and Neoxorides Clément (Poemeniinae), are recorded for the first time from Mexico. Two species are described as new to science: Perithous escondidus Khalaim & Ruíz-Cancino, sp. nov. (Mexico: Nuevo León) and Neoxorides borderai Khalaim, sp. nov. (Mexico: Hidalgo). A brief review of the North American species of Perithous and Neoxorides is given, along with identification keys for North American taxa are provided.